Uji Efektivitas Antiinflamasi Kombinasi Ekstrak Herba Seledri (Apium Graveolens L.) Dan Daun Binahong (Anredera Cordifolia (Ten.) Steenis) Pada Tikus Putih - Karina Wulan Sari; Rahmawati Raising; Novi Ayuwardhani (Pusat Riset dan Inovasi Nasional, 2023)
Inflammation is a protective response that is intended to eliminate the initial cause cell injury and cell discard and necrotic tissue caused by cell damage. Plants suspected of having anti-inflammatory properties as is Herba Celery (Apium graveolens L.) which included family Apiaceae and leaves Binahong (Anredera cordifolia (Ten.) Steenis) are included in the family basellaceae. Which act as antiinflammatory herbs binahong celery and leaves are flavonoids. This study aims to determine the effect of anti-inflammatory herb extract combination Celery (Apium graveolens L.) and leaves Binahong (Anredera cordifolia (Ten.) Steenis) against a white male rats. Herbal extract and leaf celery binahong extracted using 96% ethanol by maceration method. Animal test used was a white male rats as much as 25 animals with body weight of 100-300 grams. The test animals were divided into 5 groups: negative control group (CMC 1%), the positive control group (Diclofenac Sodium 50 mg), group combination herbal extracts celery and leaves binahong with a dose of 200 mg / kg: 200 mg / kg, 100 mg / kg: 300 mg / kg, 300 mg, kg: 100 mg / kg. Treatment 1 hour before the feet of mice induced by subplantar karagenin on the rear left foot white male rats. Edema volume measurements on the soles of mice were observed every 1 hour for 5 hours. The results showed a combination of herbal extracts and leaf celery binahong show stable results, where the hour-3 increased volumes continued in the hours 4th and 5th. Results per cent udema on a combination of herbal extracts and leaf celery binahong ie 49.13%, 44.66% and 45.92%. The average volume is used to calculate the percent edema inflammation, inflammation percent results obtained to calculate the percent inhibition.